Study on setting up a ladies' social club in Singapore. - Chang, Gayle Teresa Xiuling. (2008)
This report is a business plan encompassing a feasibility study and an in-depth market research to find out what ladies want in a social club exclusively for ladies. The club will offer entertainment and recreational services, facilities and programs specific to women’s needs and desires